Molecular evolution of glutathione S-transferases in the genus drosophila. - Low, W.Y.; Ng, H.L.; Morton, C.J.; Parker, M.W.; Batterham, P.; Robin, C. (Genetics, 2007)
As classical phase II detoxification enzymes, glutathione S-transferases (GSTs) have been implicated in insecticide resistance and may have evolved in response to toxins in the niche-defining feeding substrates of Drosophila species. We have annotated the GST genes of the 12 Drosophila species with recently sequenced genomes and analyzed their molecular evolution. Gene copy number variation is attributable mainly to unequal crossing-over events in the large delta and epsilon clusters. Within these gene clusters there are also GST genes with slowly diverging orthologs. This implies that they have their own unique functions or have spatial/temporal expression patterns that impose significant selective constraints. Searches for positively selected sites within the GSTs identified G171K in GSTD1, a protein that has previously been shown to be capable of metabolizing the insecticide DDT. We find that the same radical substitution (G171K) in the substrate-binding domain has occurred at least three times in the Drosophila radiation. Homology-modeling places site 171 distant from the active site but adjacent to an alternative DDT-binding site. We propose that the parallel evolution observed at this site is an adaptive response to an environmental toxin and that sequencing of historical alleles suggests that this toxin was not a synthetic insecticide.